HUBUNGAN KETERAMPILAN BERPIKIR KOMPUTASI DENGAN LITERASI NUMERASI SISWA SEKOLAH DASAR - Yulia Hardiyanti Saputri; Zetra Hainul Putra; Eva Astuti Mulyani (STKIP Subang, 2026)
Having computational thinking skills and numeracy literacy is a must in the era of technological development as it is today. However, there are still few studies that discuss the relationship between these two variables. The purpose of this study is to determine the form of relationship between Computational thinking skills and numeracy literacy of fifth grade students of SDIT Raudhaturrahmah. This study is a quantitative correlation study with a survey method by taking 49 respondents from all fifth grade students at SDIT Raudhaturrahmah the type of research used in this study, namely the test of computational thinking skills and numeracy literacy. in this study SDIT Raudhaturrahman Pekanbaru of 49 students who were sample objects had high computational thinking skills with an average percentage of 63.78% while literacy was in the medium category with a percentage of 57.55%. In this study From the results above, it shows that there is a significant relationship between the variables of Computational Thinking and Numeracy Literacy seen from the sign value which is <0.05. The results of this study are expected to provide an overview of computational thinking skills with numeracy literacy and are expected to be an additional reference for further researchCorrelation, computational thinking skills, numeracy literacy